2018
DOI: 10.1002/wrna.1519
|View full text |Cite
|
Sign up to set email alerts
|

The DDX5/Dbp2 subfamily of DEAD‐box RNA helicases

Abstract: The mammalian DEAD-box RNA helicase DDX5, its paralog DDX17, and their orthologs in Saccharomyces cerevisiae and Drosophila melanogaster, namely Dbp2 and Rm62, define a subfamily of DEAD-box proteins. Members from this subfamily share highly conserved protein sequences and cellular functions. They are involved in multiple steps of RNA metabolism including mRNA processing, microRNA processing, ribosome biogenesis, RNA decay, and regulation of long non-coding RNA activities. The DDX5/Dbp2 subfamily is also impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 159 publications
(364 reference statements)
2
65
0
Order By: Relevance
“…Previous results from our laboratory showed that the ortholog of DDX5 in S. cerevisiae, Dbp2 (Xing et al 2019), is required for efficient termination of RNAPII transcription, as loss of DBP2 results in accumulation of a 39 extended GAL10 mRNA and GAL10s long, noncoding RNA (Cloutier et al 2012). Both Dbp2 and DDX5 exhibit highly efficient RNA duplex unwinding in vitro, consistent with a role in altering secondary structure Xing et al 2017).…”
supporting
confidence: 55%
“…Previous results from our laboratory showed that the ortholog of DDX5 in S. cerevisiae, Dbp2 (Xing et al 2019), is required for efficient termination of RNAPII transcription, as loss of DBP2 results in accumulation of a 39 extended GAL10 mRNA and GAL10s long, noncoding RNA (Cloutier et al 2012). Both Dbp2 and DDX5 exhibit highly efficient RNA duplex unwinding in vitro, consistent with a role in altering secondary structure Xing et al 2017).…”
supporting
confidence: 55%
“…DDX17 is a member of the large family of DEAD-box RNA helicases found within the superfamily 2 ATPases Linder and Jankowsky, 2011;Xing et al, 2019). DEADbox proteins are necessary for proper function of RNA in many cellular processes (Cordin et al, 2006;Fuller-Pace, 2013b;Gustafson and Wessel, 2010;Janknecht, 2010;Jarmoskaite and Russell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other DEAD-box proteins, DDX17 is an RNA-dependent ATPase. For its helicase function, DDX17 is thought to remodel RNA in a non-processive manner (Huang and Liu, 2002;Pyle, 2008;Rö ssler et al, 2001;Xing et al, 2017Xing et al, , 2019. DDX17 has been reported to bind various RNA sequences and structures, including stem-loop structures (Mori et al, 2014;Moy et al, 2014;Remenyi et al, 2016), G-quadruplexes (Herdy et al, 2018), and R-loops (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The p68 RNA helicase (also called DEAD-box protein 5; DDX5) is a prototypic member of the DEAD box family of RNA helicases that exhibits ATPase and RNA unwinding activities 5 . The DEAD box family is named after the amino acid sequence of its conserved Motif II (also known as the Walker B motif) containing the amino acids asp-glu-ala-asp (D-E-A-D).…”
Section: Introductionmentioning
confidence: 99%